Comparative Analysis of Development Administration Models Between Developed and Developing Countries - Wahyudi Mokobombang; Khaeriyah, Khaeriyah (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This research compares development administration models between developed and developing countries. Using comparative analysis, this study evaluates policies and best practices from both contexts. Research findings reveal significant differences in development approaches and outcomes, as well as implications for policy development. The analysis demonstrates that developed countries predominantly employ post-bureaucratic, participatory, and innovation-driven models characterized by strong institutional capacity, high levels of digitalization, decentralized decision-making, and robust accountability mechanisms. In contrast, developing countries frequently rely on hybrid models combining traditional bureaucratic structures with nascent reforms, constrained by limited resources, capacity gaps, institutional weaknesses, and political economy challenges. Critical differentiators include governance quality, administrative capacity, technological infrastructure, resource availability, stakeholder participation levels, and policy implementation effectiveness. Despite contextual differences, successful development administration in both settings shares common elements, including political commitment, adaptive capacity, citizen engagement, evidence-based policymaking, and continuous learning mechanisms. The research identifies transferable lessons and contextual adaptation requirements for developing countries seeking to enhance their development administration systems.